2003
DOI: 10.1097/01.ss.0000095143.68539.55
|View full text |Cite
|
Sign up to set email alerts
|

PHOSPHORUS RETENTION BY THE Ap HORIZON OF A SPODOSOL AS INFLUENCED BY CALCIUM AMENDMENTS 1

Abstract: The low capacity of acid sandy soils to bind P is one reason for the leaching and runoff of P from these soils. Various soil amendments have been used to reduce P leaching. This study was conducted to show the effect of CaCO 3 , dolomite, gypsum, and CaCl 2 on P retention by the Ap horizon of a Spodosol. Phosphorus sorption was studied in a batch experiment at an initial P concentration range of 0 to 10 mg L ؊1 . The amendment rate used was 0.05 mmol of either Ca or Ca ؉ Mg (and also 0.1 mmol in the case of Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…To conclude, the contrast in effectiveness of lime and gypsum, and the observed increases in RP solubility in limed soils with the largest pH increases, suggest that any effectiveness of these two source measures is due largely to increases in Ca concentration, rather than pH. Boruvka and Rechcigl (2003) concluded that lime and gypsum were effective as P source measures due to increased Ca concentrations but, in contrast to this study, they concluded that an increase in pH was also required. pH in limed soils in their study reached 7.4 and 7.8.…”
Section: Reactive Phosphorusmentioning
confidence: 49%
See 2 more Smart Citations
“…To conclude, the contrast in effectiveness of lime and gypsum, and the observed increases in RP solubility in limed soils with the largest pH increases, suggest that any effectiveness of these two source measures is due largely to increases in Ca concentration, rather than pH. Boruvka and Rechcigl (2003) concluded that lime and gypsum were effective as P source measures due to increased Ca concentrations but, in contrast to this study, they concluded that an increase in pH was also required. pH in limed soils in their study reached 7.4 and 7.8.…”
Section: Reactive Phosphorusmentioning
confidence: 49%
“…Although it is often neglected in studies of P source measures and P loss in general (Boruvka and Rechcigl 2003;Callahan et al 2002;Stout et al 2003;Torbert et al 2005), OP can be an important fraction in soil solution and P loss (Murphy 2007;Toor et al 2003). Organic P can become bio-available and contribute to eutrophication in receiving water bodies through chemical or enzymatic hydrolisation (Correll 1998).…”
Section: Organic Phosphorusmentioning
confidence: 98%
See 1 more Smart Citation
“…They also found constructing a 0.73-ha (1.80-ac) windrow composting pad from lime and fly ash materials was approximately 28% of the cost of a comparable-size 15-cm (6.0-in) thick concrete pad. Another potential benefit of fly ash and lime composting pad materials is the P-sorbing properties reported by many researchers (Dou et al 2003;Boruvka and Rechcigal 2003;Lau et al 2001;Brauer et al 2005;DeLaune et al 2006;Penn and Bryant 2006). Dou et al (2003) found fly ash reduced soluble P by 60% from converting water soluble phosphorus (H 2 O-P) in dairy manure to sodium bicarbonate-extractable phosphorus (NaHCO 3 -P), a fraction less vulnerable to RO losses.…”
mentioning
confidence: 99%
“…[23,35] At higher pH, phosphorus forms insoluble calcium phosphate, which precipitated and reduced transport. [21,35,36] In an amendment study by Boruvka and Rechcigl, [37] pH was raised to 7.4-7.8 by CaCO 3 and resulted in higher P sorption. Boruvka and Rechcigl [37] and other researchers [38,39] concluded that the Ca ion provided must be accompanied with an increase in pH for direct precipitation and sorption.…”
Section: Runoff Eventmentioning
confidence: 99%